Who Really Controls Greenwashing? The Interplay of Ownership Concentration and Corporate Governance: Evidence from High-Environmental-Impact Sectors in Indonesia - Zera Ayudiastika; Islahuddin; Yossi Diantimala (ccounting Department, Universitas Syiah Kuala, Indonesia, 2026)
This study examines whether ownership concentration reduces greenwashing and whether corporate governance strengthens this relationship. The sample consists of 752 firm-year observations from energy, basic materials, and industrial companies listed on the Indonesia Stock Exchange during 2020-2024. The findings reveal that ownership concentration is negatively associated with greenwashing, indicating that dominant shareholders play an effective monitoring role in constraining opportunistic sustainability disclosure. Furthermore, corporate governance strengthens the negative relationship between ownership concentration and greenwashing. These results highlight the complementary roles of ownership structure and governance mechanisms in enhancing corporate sustainability accountability. This study contributes to the greenwashing literature by providing evidence from environmentally sensitive industries in an emerging market context.